2006
DOI: 10.1038/sj.onc.1210088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Akt inhibition on scatter factor-regulated gene expression in DU-145 human prostate cancer cells

Abstract: The cytokine scatter factor (SF) (hepatocyte growth factor) transduces various biologic actions, including cell motility, invasion, angiogenesis and apoptosis inhibition. The latter is relevant to understanding the role of SF in promoting tumor cell survival in different contexts, for example, detachment from basement membrane, growth in metastatic sites and responses to chemo-and radiotherapy. Previously, we showed that SF protects cells against apoptosis owing to DNA damage, by a mechanism involving phosphoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…We previously showed that transfection of this vector into DU-145 blocks SF-induced Akt phsophorylation as well as the phosphorylation of several Akt substrates (e.g. GSK3 and mTOR) [20]. As shown in Fig.…”
Section: Scatter Factor Inhibits Trail-mediated Apoptosismentioning
confidence: 76%
See 2 more Smart Citations
“…We previously showed that transfection of this vector into DU-145 blocks SF-induced Akt phsophorylation as well as the phosphorylation of several Akt substrates (e.g. GSK3 and mTOR) [20]. As shown in Fig.…”
Section: Scatter Factor Inhibits Trail-mediated Apoptosismentioning
confidence: 76%
“…Previously, we reported that Akt is required for SF protection of carcinoma and glioma cells against DNAdamaging agents, such as ADR [18][19][20][21]33,34]. Here, we tested whether Akt signaling is required for protection against TRAIL, by the use of a DN-Akt expression vector that encodes a kinase-dead point mutant Akt (K179A).…”
Section: Scatter Factor Inhibits Trail-mediated Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…[100][101][102] Transmembrane receptor in combination with tyrosine kinase regulates signal transduction. [109][110][111][112] Moreover, c-Met can bind to Fas and block Fas ⁄ Fas-ligand co-intraction and thus prevents cell death. 103 Many papers have reported that c-Met and HGF are expressed together.…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%
“…Survival signal transduction such as MAPK, PI3K-Akt, and NF-jB are responsible for anti-apoptotic characters of c-Met. [109][110][111][112] Moreover, c-Met can bind to Fas and block Fas ⁄ Fas-ligand co-intraction and thus prevents cell death. 113,114 However, apoptotic effects of HGF ⁄ c-Met is not yet fully understood, but it has been observed in number of cell lines such as ovarian carcinoma cell, breast carcinoma cell, mouse sarcoma cell, and mouse hepatocarcinoma cell.…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%